Music-listening as an intervention for chronic pain relief : a case study - Campbell, Elsa (2014)
The field of audioanalgesia is vast. Research shows a combination of pharmacology and music interventions helps to reduce anxiety and stress, resulting in lower levels of pain, pre- and post-operatively. This study is an exploration of the use of music-listening as a method of pain relief with the knowledge that certain types of music aid in reaching altered states of consciousness. In reaching this state of relaxation, the realisation one’s own methods of pain management and goals towards better health are easier. This paper also discusses the importance of collaboration between various ways of practicing medicine, as well as how vital it is to be aware of one’s body and external stresses which can affect well-being. Taking time for oneself is shown to be extremely beneficial for those suffering from chronic pain, but also for the participant of this study in particular.